Biomechanical properties of synthetic surgical meshes for pelvic prolapse repair. (March 2016) - Todros, S.; Pavan, P.G.; Natali, A.N.
Abstract: Synthetic meshes are widely used for surgical repair of different kind of prolapses. In the light of the experience of abdominal wall repair, similar prostheses are currently used in the pelvic region, to restore physiological anatomy after organ prolapse into the vaginal wall, that represent a recurrent dysfunction. For this purpose, synthetic meshes are surgically positioned in contact with the anterior and/or posterior vaginal wall, to inferiorly support prolapsed organs. Nonetheless, while mesh implantation restores physiological anatomy, it is often associated with different complications in the vaginal region. These potentially dangerous effects induce the surgical community to reconsider the safety and efficacy of mesh transvaginal placement. For this purpose, the evaluation of state-of-the-art research may provide the basis for a comprehensive analysis of mesh compatibility and functionality. The aim of this work is to review synthetic surgical meshes for pelvic organs prolapse repair, taking into account the mechanics of mesh material and structure, and to relate them with pelvic and vaginal tissue biomechanics. Synthetic meshes are currently available in different chemical composition, fiber and textile conformations. Material and structural properties are key factors in determining mesh biochemical and mechanical compatibility in vivo. The most significant results on vaginal tissue and surgical meshes mechanical characterization are here reported and discussed. Moreover, computational models of the pelvic region, which could support the surgeon in the evaluation of mesh performances in physiological conditions, are recalled.